Company Management: The Influence of Organizational Structure and Leadership on Team Performance - Fatimah Malini Lubis; Ita Soegiarto; Pawisari; Koko Haryono; Syamsurizal (PT Inovasi Pratama Internasional, 2024)
This research is driven by a need to gain insight into the key roles that effective leadership plays in achieving optimal performance within teams. In order to fully comprehend the dynamics of team leadership, it is essential to have a robust theoretical and conceptual framework in place. This understanding will help us to identify the factors that influence team performance, and in particular, the role that effective communication, positive feedback, rewards and recognition, and the creation of a supportive work environment plays in motivating teams. In addition, it is vital to consider the key factors that influence the performance of high-functioning teams, which include elements such as team trust, collaboration, effective communication, and leader support. This research employs the methodology of a literature study to ascertain the role of leadership in organizations. In conclusion, team leadership plays an essential role in achieving effective team performance in organizations. By developing a robust theoretical and conceptual framework, leaders can cultivate the practical and strategic insights necessary to lead teams effectively. Effective leaders influence team performance motivation, manage conflict, build cooperation, and create a supportive work environment. The significance of effective team performance is also evidenced by the key factors that influence great team performance. In practice, leaders must be able to apply these insights in a practical manner in order to achieve the desired results.